A GIS-based shape index for land parcels - Demetriou, Demetris; Stillwell, John; See, Linda (My University, 2013)
Shape analysis is of interest in many fields of spatial science and planning including land management in rural areas. In particular, evaluating the shape of existing land parcels is critical when implementing rural development schemes such as land consolidation. However, existing land parcel shape indices have major deficiencies: completely different shapes of parcels may have the same index value or similar parcel shapes may have different index scores. Thus, there is a clear requirement for a more accurate and reliable measurement method. This paper therefore presents a new parcel shape index (PSI) which integrates a geographical information system (GIS) with a multi-attribute decision-making (MADM) method. It involves the amalgamated outcome of six geometric measures represented by value functions involving a mathematical representation of judgements by experts that compare each geometric measure with that of an optimum parcel shape defined for land consolidation projects. The optimum shape has a PSI value of 1 while the worst shape has a value close to 0. The shape measures used in the model include length of sides, acute angles, reflex angles, boundary points, compactness and regularity. The paper uses data for two case study areas in Cyprus to demonstrate the superiority of the new PSI over three existing shape indices employed in other studies. The methodology utilized here can be implemented in other disciplines dealing with the assessment of objects that can be compared to an optimum. © 2013 SPIE.
Keywords: ArcGIS; Cyprus; land consolidation; multi-attribute decision making; parcel shape index (PSI); Shape analysis